Green roof recent designs to runoff control: A review of building materials and plant species used in studies - Leite, Florence Rezende [UNESP]; Antunes, Maria Lúcia Pereira [UNESP] (Elsevier, 2023)
Green roof is one of the main infrastructures used in Sustainable Urban Drainage Systems (SUDS). Detailed design and the correct choice of materials to be applied in this type of roof are essential to obtain satisfactory hydrological performance. In recent years, numerous papers on this topic have been published. This study aimed to provide a holistic view of the main research trends for the construction of green roofs to control stormwater runoff. A systematic literature review was carried out within scientific publications from the last 5 years in the Web of Science (WoS) database. 67 papers were selected for analysis. Recent types of vegetation and materials for green roofs were listed and hydrological tests were discussed in this review. Extensive substrates were chosen by 78% of the studies due to smaller thickness, tending to be lighter and economically viable than intensive substrates. Succulents of Sedum genus were the most used in the studies due to their physiological characteristics and ability to adapt to different climates. Drainage layer consisted mainly of specific slabs commercially available for green roofs. Other layers, such as filtration, thermoacoustic insulation, and waterproofing, were also applied in many studies. The main parameters to evaluate the hydrological performance were retention capacity and runoff coefficient. In general, results showed that green roofs have considerable capacity to reduce rainwater runoff. However, many factors, such as meteorological indices, substrate antecedent moisture, and materials and plant species used can influence hydrological performance of green roofs. Some gaps were found in studies. Most of them did not compare the performance of green roofs with conventional roofs. In addition, the studies did not present cost and weight analyses, which is very important for the decision to build green roofs.
Keywords: Design; Green cover; Materials; Plant species; Runoff control